1.What will be the result when x = 2 and y = -3 in algebraic expression: 2x – 2y + 4
a. -14 b.-6 c. 6 d. 14
2.What will be the result when x = -1 and y = 2 in algebraic expression: 5x – y
a. -11 b. -7 c. 7 d. 11
3.The result of an algebraic expression: 5ab when a = 3 and b = -2
a. -30 b. -10 c. 10 d. 30
4.When the algebraic expression: 2a – b + 3 is evaluated with a = -1 and b = 2, what is the result?
a. -7 b. -1 c. 1 d. 7
5.The frst step in evaluating algebraic expressions is _________ the give values for each variable.
a. simplify b. evaluate c. translate d. substitute
![1What Will Be The Result When X 2 And Y 3 In Algebraic Expression 2x 2y 4a 14 B6 C 6 D 142What Will Be The Result When X 1 And Y 2 In Algebraic Expression 5x Y class=](https://ph-static.z-dn.net/files/dda/c53d3942e603dab195f3f959d0db38ed.jpg)